A taxonomic revision of the Madagascar-endemic longhorn beetle genus Tsivoka Villiers (Coleoptera: Cerambycidae) with the description of a new species - Jeong, Soo-Hyun; Vives, Eduard; Mckenna, Duane D. (Zootaxa, 2025)
The longhorn beetle tribe Dorcasomini exhibits remarkable endemism and species richness in Madagascar. Among the diurnal genera of Dorcasomini, Tsivoka Villiers, 1982 (Coleoptera: Cerambycidae) is distinguished by its coloration and elytral patterning. In this study, we present a taxonomic review focusing on Tsivoka, identifying a total of four species, including one species new to science: T. humeralis sp. nov.; T. peyrierasi Villiers, 1982; T. simplicicollis (Gahan, 1890); and T. testaceipes (Fairmaire, 1889). Descriptions, photographs, and a taxonomic key are provided for species identification. Additionally, we provide a distribution map for each species based on specimen information.